Accounting in Marketing Perspective Training Batch III, Sekolah Bisnis dan Manajemen – Institut Teknologi Bandung (SBM-ITB) - Wiwiek Mardawiyah Daryanto (Journal of Sustainable Community Development (JSCD), 2021)
Managerial accounting is an activity or process that produces information that is useful for management for making economic decisions in carrying out management functions. Sekolah Binis dan Manajemen – Institut Teknologi Bandung (SBM-ITB) collaborated with the MarkPlus Institute to carry out the OMNI MBA Program 2020 Batch III on February 5, 2021. Out of the twelve subject topics contained in the program, one of them is entitled Accounting in Marketing Perspective that scheduled on Friday, 5 February 2021 with the author as the facilitator. The subjects include the Break-Even Point (BEP) theory, the Cost Classifications theory with the concept of Different Cost for Different Purposes, as well as related case studies. This training is expected to increase the competence and productivity of company managers in maximizing their role. This training went smoothly because of the strong enthusiasm of the participants. In addition, the inhibiting factor is the limited training time.